Stitz-Zeager_College_Algebra_e-book

If we attempt to build a table directly we quickly

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: and wish to find the point on y = j (x) = f (−x + 3) which corresponds to (4, 2). We set −x + 3 = 4 and solve. Our first step is to subtract 3 from both sides to get −x = 1. Subtracting 3 from the x-coordinate 4 is shifting the point (4, 2) to the left. From −x = 1, we then multiply5 both sides by −1 to get x = −1. Multiplying the x-coordinate by −1 corresponds to reflecting the point about the y -axis. Hence, we perform the horizontal shift first, then follow it with the reflection about the y -axis. Starting with √ f (x) = x, we let j1 (x) be the intermediate function which shifts the graph of f 3 units to the left, j1 (x) = f (x + 3). y y (1, 2) (4, 2) 2 2 (−2, 1) (1, 1) 1 1 (−3, 0) (0, 0) −4 −3 −2 −1 1 y = f (x) = 2 √ 3 4 x shift left 3 units −4 −3 −2 −1 1 2 −− − − − −→ −−−−−− x subtract 3 from each x-coordinate y = j1 (x) = f (x + 3) = 3 √ 4 x x+3 To obtain the function j , we reflect the graph of j1 about y -axis. Theorem 1.4 tells us we...
View Full Document

This note was uploaded on 05/03/2013 for the course MATH Algebra taught by Professor Wong during the Fall '13 term at Chicago Academy High School.

Ask a homework question - tutors are online